Curriculum Fidelity of English Language Teaching Teachers and Factors Affecting Teachers’ Implementation at Ethiopian Public Universities’ Context - Anteneh, Baye Ashebir; Anshu, Alemu Hailu (Educational Challenges, 2024)
This study aimed to explore English Language Teaching (ELT) teachers’ fidelity to the designed freshman English curriculum. A mixed method research design, where the quantitative data served to support the qualitative one, was used in the study. A . One-to-one interviews, observations, and post-observation interviews were used as data collection instruments. Verbatim transcription was made for the qualitative data. Then, the relevant data was categorized and the data not relevant to the present purpose was bracketed. Categories seemed to be mutually exclusive, however, and analysis was made by making connections between or among the various categories. The result showed that ELT teachers followed the fidelity perspective by adhering to the contents of the official curriculum even in circumstances where adaptations were required. However, teachers’ fidelity to the designed curriculum or to the official curriculum was offset by teachers decision to skip certain activities. ELT teachers’ adherence was imposed by different factors, including a high-stakes exam, alignment problems with instruction and assessment, the use of students’ scores for placement, relevance and repetition of activities, and lack of training. Personal/teacher factors (teachers’ beliefs, confidence, knowledge, and skills in improving the curriculum) and student factors (motivation and interest) also had significant influence. It can be concluded that ELT teachers missed one of the significant professional roles they could play during curriculum implementation – adapting contents based on the classroom context. Professional development training should be proffered to ELT teachers. In addition, institutional needs and teachers’ freedom to improve the curriculum at the classroom level need to be balanced.